Numerical Analysis on Flexibility of Unexpanded Balloon-Expandable Stent - Ilham Agung Aribowo; Varien Janitra Nuralif Susanto (JMES The International Journal of Mechanical Engineering and Sciences, 2022)
A stent is a mesh of micro metal tube commonly used to provide support to an enlarged blood vessels that are narrowed due to plaque growth. To function correctly, a stent must have specific characteristics, which includes good flexibility. The flexibility of the stent can be predicted using the finite element method simulation. The type of stent studied are the sinusoidal and spiral type balloon-expandable stent. The 3D model is created in Solidworks 2016, while the structural analysis is performed with ANSYS Workbench Student R18. The simulation carried out is a four-point bending test. The analyzed parameters are the von Mises stress and the flexibility value of the stent. The material model for the stent is isotropic SS 316 L, while the balloon was polyurethane which is modeled as hyper-elastic material. The results obtained from this study are sinusoidal type stents can be deflected up to 0.221 mm to remain in the elastic area, while spiral type stents can be deflected up to 0.109 mm. The maximum flexibility value of the sinusoidal type stent is 0.003526 N-1.mm-2 while the spiral type stent is 0.002478 N-1.mm-2.